Media Literacy: Agenda Ã¢â‚¬Å“PendidikanÃ¢â‚¬Â Nasional yang Terabaikan - ., Rahayu (FISIP Universitas Atma Jaya Yogyakarta, 2004)
The complexcity of the media’s problem in determining media policy can not be solved only by structural approach. The cultural approach is also needed in getting people participation and involvement to solve that problem. When the effect of media become an important issue in the relationship between media and the public, the media should not only be regulated, but the public should be involved and given the opportunity to play important role making the media to be part of public life and helping the public to solve their life. People’s empowerment in this cultural approach can be conducted through the program of media literacy. This movement as a public power and identity certainly has influence to the media.